2020
DOI: 10.1152/ajprenal.00521.2019
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 mediates early renal leukocyte infiltration during salt-sensitive hypertension

Abstract: Studies examining mechanisms of Dahl salt-sensitive (SS) hypertension have implicated the infiltration of leukocytes in the kidneys, which contribute to renal disease and elevated blood pressure. However, the signaling pathways by which leukocytes traffic to the kidneys remain poorly understood. The present study nominated a signaling pathway by analyzing a kidney RNA sequencing data set from SS rats fed either a low-salt (0.4% NaCl) diet or a high-salt (4.0% NaCl) diet. From this analysis, chemokine (C-C moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…A HSD increased CCL3's expression, but no reduction was detected in the melatonin treated rats. A recent study in the same model has shown that a HSD upregulates CCL2 in the kidney by using the RNA-Seq method [39]. However, this study tested the levels on days 3 and 21 after the diet started.…”
Section: Discussionmentioning
confidence: 98%
“…A HSD increased CCL3's expression, but no reduction was detected in the melatonin treated rats. A recent study in the same model has shown that a HSD upregulates CCL2 in the kidney by using the RNA-Seq method [39]. However, this study tested the levels on days 3 and 21 after the diet started.…”
Section: Discussionmentioning
confidence: 98%
“…Alsheikh et al. demonstrated that CCL2/CCR2 was important in the early recruitment of leukocytes in rat hypertension kidney damage model [ 31 ]. In a clinical setting, Puthumana et al.…”
Section: Discussionmentioning
confidence: 99%
“…This observation as well as the corresponding increase of M1 macrophage infiltration was to be expected from previous reports from the same model [ 13 ]. Others have previously shown that blockade or deficiency of CCL2 ameliorates mononuclear cell infiltration and target organ damage in renovascular or other forms of hypertension [ 30 , 31 ]. These data are certainly compatible with a role for macrophage infiltration in the development of malignant hypertension, but the parallel increase of M2 macrophage infiltration should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%